Transvaginal Sonographic Assessment of the Follicular Development and Endometrial Thickness in Spontaneous and Clomiphene Citrate-Induced Cycles - Esmat Baroti; Elham Neisan Samani (Tehran University of Medical Sciences, 2008)
Objective: To assess follicular development and endometrial growth using transvaginal sonography in spontaneous and clomiphene citrate induced (CC) cycles. Materials and methods: One hundred consecutive couples with unexplained infertility were recruited for this cross sectional study from 2003 to 2005. Patients were monitored for the first cycle with no medication while the laboratory routine test results were being prepared. Clomiphene citrate (150 mg) was administered on days 5 to 9 of cycle in 60 women. The pattern of the follicular development and endometrial growth was evaluated between clomiphene citrate-induced cycles and spontaneous cycles. SPSS software and student t test were used for analyzing the results. P value less than 0.05 was considered for statistical significance. Results: The patterns of follicular development and endometrial growth were similar in both study cycles. Conclusion: Clomiphene citrate-induced cycles did not show different follicular and endometrial growth patterns compared with spontaneous cycles, so this must be regarded in treatment decision making.